2021
DOI: 10.3233/bme-201151
|View full text |Cite
|
Sign up to set email alerts
|

The expression of two collagen receptor subfamilies, integrins and discoidin domains during osteogenic and chondrogenic differentiation of human mesenehymal stem cells

Abstract: BACKGROUND: Collagen receptors are characterized by binding to and being activated by collagens. We know little about the molecular mechanism by which the integrins and discoidin domains (DDRs) recognize collagen. OBJECTIVE: The aim of this study was to investigate the expression of two main collagen receptor subfamilies, integrins and DDRs, during osteogenic and chondrogenic differentiation of human mesenehymal stem cells (hMSCs). METHODS: Using qRT-PCR, Western blots and FACS, the levels of DDR1, DDR2, integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The expression of DDR2 and integrin α11β1 was increased when human bone marrow MSC were cultured on a substrate with type 1 collagen. It was found that the expression of integrin α11β1 prevailed during chondrogenic differentiation, while the expression of DDR2 was also significantly higher during osteogenic differentiation [ 84 ].…”
Section: Ecm Receptor Signaling Pathways During Msc Differentiationmentioning
confidence: 99%
“…The expression of DDR2 and integrin α11β1 was increased when human bone marrow MSC were cultured on a substrate with type 1 collagen. It was found that the expression of integrin α11β1 prevailed during chondrogenic differentiation, while the expression of DDR2 was also significantly higher during osteogenic differentiation [ 84 ].…”
Section: Ecm Receptor Signaling Pathways During Msc Differentiationmentioning
confidence: 99%
“…There are at least 18 α subunits and 8 β subunits in humans, which together generate 24 integrin proteins. Among them, integrin β1 (ITGB1) is the hub subunit, which can combine with other 12 α subunits like α2β1 and α11β1 integrin [ 20 ], and it belongs to the integrin family mainly associated with chondrogenesis [ 21 , 22 ]. The integrin β binds to the domain of TGF-β precursor to activate TGF-β precursor to eventually release the mature TGF-β growth factor that contributes to chondrogenesis [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%